Characterization of the Scientific Output of Health Professionals from Cienfuegos Visible in the Scopus Database - Yuniet Rojas Mesa; María Elinor Dulzaides Iglesias; Ana María Molina Gómez; Carlos Caballero Díaz (Medisur)
Background: the publication of the results from scientific research and projects ensures dissemination of science, exchange, feedback and update of its trends. Objective: to characterize the scientific output of health professionals from Cienfuegos visible in the Scopus database. Methods: a descriptive study was conducted in the Provincial Medical Sciences Information Center including the publications by health professionals from Cienfuegos visible in the Scopus database from January 2007 to September 2013. The variables analyzed were: publications per year, topics discussed in the publications, most prolific authors, collaboration among institutions and countries as well as institutions according to the authors' affiliation. Results: 102 papers were retrieved, mostly by authors working in secondary care, specifically at the Gustavo Aldereguía Lima Provincial Hospital. A total of 141 authors are represented, 82 times as first authors and 230 as co-authors. Only 9.2 % appears five or more times. Most common topics are: cardiovascular diseases and public health. Collaboration with 13 institutions (nine papers with four national institutes and 30 with foreign institutions) was observed. Conclusions: scientific output of health professionals from Cienfuegos visible in the Scopus database is still scant.